Neisseria Gonorrhoeae Susceptibility to -lactamics Antibiotic, Tetraciclines, and Quinolones - Marisol Sandoval; Armando Guevara; Lumar Ward; Ramos Regina; Yuraima Suarez; Marlly Salomon (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Neisseria gonorrhoeae susceptibility to -lactamics antibiotic, tetraciclines, and quinolones was studied in strains isolated from patients with gonococcic cervicitis and/or urethritis that were to consultation of Infections of Sexual Transmission of The Ambulatory Urban type II, in a neighborhood of Ciudad Bolívar from July to August - 2003. The samples were seeded in Agar Blood, GC Agar Base and 1% defined growth supplement, Agar Thayer Martin; making simultaneously a Gram stain. Suspicious colonies were identified by means of oxidase test and sugar degradation in CTA medium. The production of -lactamases was investigated of by means of the acidimetric method. Susceptibility tests were made in GC Agar Base and 1% defined growth supplement. Penicilline, ceftriaxone, tetracicline, and Ciprofloxacin were used. 50 strains were isolated of Neisseria gonorrhoeae that represented 43.85% of patients with gonococci infections (Urethritis and/or cervicitis) of which 82% belonged to masculine sex. There was no evidence of production of ß-lactamases in the studied strains. As far as the susceptibility to the antimicrobial drugs it was found 46% strains resistant to penicillin, 42% to tetraciclines. Ceftriaxone and ciprofloxacin showed a good activity against N. gonorrhoeae with 98 and 92% of sensitivity, respectively.